Analysis of Influencing Factors on Splitting Characteristics of Hydraulic Asphalt Concrete - ZHANG Yang (Renmin Zhujiang)
Mix ratio design and analysis of asphalt concrete are an important way to study its physical and mechanical properties.This paper performs 16 sets of tests with 3 factors and 4 levels according to the orthogonal test design theory,and discusses the influence of gradation index,filler amount and asphalt content on the splitting strength and splitting displacement by the range and variance analysis method to obtain the optimum combination of mix parameters,spatializes the mix ratio parameters,and analyzes the distribution law of asphalt concrete splitting characteristics.The test results show that:The influence of the mix parameters on the splitting strength of asphalt concrete decreases in order of gradation index,filler amount and asphalt content,while contrary to the splitting displacement.In terms of strength,the gradation index is considered preferentially for the splitting strength of asphalt concrete;while from the perspective of stiffness,the asphalt content is preferential for that.When selecting asphalt concrete as an impermeable body in engineering parts where hydraulic fracturing may exist,with full consideration to the stress state,the suitable mix ratio should be used.